Informacja w radiu komercyjnym - Garcarek, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
This article concerns information and information services in the modern stations of commercial radios. It includes types of messages, information and news used in radio programs.